Do remote dialysis services really cost more? An economic analysis of hospital and dialysis modality costs associated with dialysis services in urban, rural and remote settings - Gillian Gorham; Kirsten Howard; Joan Cunningham; Federica Barzi; Paul Lawton; Alan Cass (BMC, 2021)
Plain language summary Most people requiring ongoing treatment for end-stage kidney disease in the Northern Territory (NT) identify as Aboriginal with the majority residing in areas classified as remote or very remote. Unlike other jurisdictions in Australia, haemodialysis in a satellite unit is the most common form of treatment. However, there is a geographic mismatch between demand and service provision, with services centralised in urban areas. Patients and communities have long advocated for services at or closer to home, maintaining that the consequences of relocation and dislocation have far reaching health, psychosocial and economic ramifications. We analysed retrospective hospital data for 995 maintenance dialysis patients, stratified by the model of care they received in urban, rural and remote locations. Using cost weights attributed to diagnosis codes, we costed hospital admissions, emergency department presentations and maintenance dialysis attendances, to provide a mean total health service cost/patient/year for each model of care. We found that urban services were associated with low observed maintenance dialysis and high hospital costs, but the inverse was true for remote and very remote models. Remote models had high maintenance dialysis costs (due to expense of remote service delivery and good dialysis attendance) but low hospital usage and costs. When adjusted for other variables such as age, dialysis vintage and comorbidities, lower total hospital costs were associated with rural and remote service provision. In an environment of escalating demand and constrained budgets, this study underlines the need for policy decisions to consider the full cost consequences of different dialysis service models.